Perlindungan Hukum bagi Pemegang Polis dalam Penyelesaian Klaim Asuransi Jiwa - Haris Budiman; Bias Lintang Dialog; Iman Jalaludin Rifa’i; Peny Hanifah (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2022)
An insurance agreement occurs where the policyholder transfers the risk to the insurance company. Legal protection regarding to life insurance policy holders is regulated in the Law of the Republic of Indonesia Number 40 of 2014 concerning Insurance. Life insurance claims are in the form of claims from the insured party where the policy holder asks for his rights in the life insurance policy agreement to make payments on the life insurance benefits. This study aims to determine the legal protection for life insurance policy holders and the procedure for settlement of life insurance claims. Life insurance claims often have difficulty in filing, because the company has standards in submitting claims listed in the provisions of the life insurance policy book. Therefore, if the claim submitted by the policyholder has met the specified requirements, the life insurance claim will be unlikely to be rejected. The formulation of the problems in this study are how to regulate legal protection for life insurance policy holders in Indonesia, and how the procedure for resolving insurance claims is for life insurance policy holders. The research method used is descriptive-analytical with a normative juridical approach. The results of the study indicate that the regulation regarding legal protection for life insurance policy holders is regulated in the Law of the Republic of Indonesia Number 40 of 2014 concerning Insurance which is described in the Government Regulation of the Republic of Indonesia Number 87 of 2019 concerning Insurance Companies in the Form of Joint Ventures and other implementing regulations. The insurance claim settlement procedure for life insurance policy holders can be carried out if it is in accordance with what is stated in the standard clauses or provisions of the life insurance policy agreement.